2022
DOI: 10.1002/tcr.202100329
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic Frameworks Derived Electrocatalysts for Oxygen and Carbon Dioxide Reduction Reaction

Abstract: The increasing demands of energy and environmental concerns have motivated researchers to cultivate renewable energy resources for replacing conventional fossil fuels. The modern energy conversion and storage devices required high efficient and stable electrocatalysts to fulfil the market demands. In previous years, we are witness for considerable developments of scientific attention in Metal‐organic Frameworks (MOFs) and their derived nanomaterials in electrocatalysis. In current review article, we have discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 265 publications
0
7
0
Order By: Relevance
“…Numerous studies have been reported to fully demonstrate that MOFs have become excellent precursors and templates for most metal/metal oxides/metal hydroxides/porous carbon nanocomposites, and as-prepared 2D MOF nanosheets can also be carbonized to their corresponding 3D mixed metal oxides@porous carbon arrays on various conductive substrates, which can directly serve as an ideal electrode to be applied to electrochemical testing. In particular, the MOF-derived porous carbon obtained after pyrolysis can not only promote the accessibility of catalytically active sites but also improve the electrical conductivity, resulting in a significant improvement in catalytic performance. The samples were continuously annealed at 600 °C for 2 h (named UNi-MOFNs-2@NC, Ni-MOFNs-50@NC, and Ni-MOFNs-100@NC) with a kind of indexable metallic Ni phase of a strong and wide diffraction peak attributed to amorphous carbon. The overall morphologies of UNi-MOFNs-2@NC were characterized by SEM (Figures a and S7).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have been reported to fully demonstrate that MOFs have become excellent precursors and templates for most metal/metal oxides/metal hydroxides/porous carbon nanocomposites, and as-prepared 2D MOF nanosheets can also be carbonized to their corresponding 3D mixed metal oxides@porous carbon arrays on various conductive substrates, which can directly serve as an ideal electrode to be applied to electrochemical testing. In particular, the MOF-derived porous carbon obtained after pyrolysis can not only promote the accessibility of catalytically active sites but also improve the electrical conductivity, resulting in a significant improvement in catalytic performance. The samples were continuously annealed at 600 °C for 2 h (named UNi-MOFNs-2@NC, Ni-MOFNs-50@NC, and Ni-MOFNs-100@NC) with a kind of indexable metallic Ni phase of a strong and wide diffraction peak attributed to amorphous carbon. The overall morphologies of UNi-MOFNs-2@NC were characterized by SEM (Figures a and S7).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to catalyze chemical processes using this huge surface area, such as the synthesis of hydrogen fuel. [1][2][3] MOFs can be used to detect the presence of various compounds, including poisons or pollutants. The sort of metal ions and organic linkers utilized to create MOFs may be changed to alter their tunable qualities.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have a lot of surface area that is exposed to the environment due to their big internal surface area. It is possible to catalyze chemical processes using this huge surface area, such as the synthesis of hydrogen fuel [1–3] . MOFs can be used to detect the presence of various compounds, including poisons or pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported a Co 3 O 4 nanoparticle on carbon nanotubes (Co 3 O 4 /CNTs) with E 1/2 = 0.83 V in an alkaline solution. Transition metal-based nitrogen-codoped carbon materials (M-N-C, M = Fe, Co, Cu, Mn, and Ni) have high activity, low cost, and a wide availability of raw materials, making them a promising catalyst. Wu et al reported a Fe-N-C catalyst with a carbon nanotube that has a good effect under alkaline conditions. Najam et al reported a P, N double-doped carbon skeleton-supported monatomic Zn catalyst (Zn–N 4 P/C) has better activity ( E 1/2 = 0.86 V) and stability than Pt/C.…”
Section: Introductionmentioning
confidence: 99%